2011
DOI: 10.1103/physrevb.84.035452
|View full text |Cite
|
Sign up to set email alerts
|

Structural, mechanical, and electronic properties of defect-patterned graphene nanomeshes from first principles

Abstract: Motivated by the state of the art method for fabricating high-density periodic nanoscale defects in graphene, the structural, mechanical, and electronic properties of defect-patterned graphene nanomeshes including diverse morphologies of adatoms and holes are investigated by means of first-principles calculations within density functional theory. It is found that various patterns of adatom groups yield metallic or semimetallic, even semiconducting, behavior and specific patterns can be in a magnetic state. Eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(58 citation statements)
references
References 53 publications
2
56
0
Order By: Relevance
“…For generality and to compare energy scales, we take into account a mass gap in the dispersion relation, which can be experimentally created, e.g., due to A-B sublattice asymmetry caused by SiC substrate or by regular deposition of impurities. 20,21 At zero magnetic field it was demonstrated that the pseudospin degree of freedom (due to valleys) produces diamagnetic susceptibility which is [22][23][24] …”
Section: Clean Graphene With Possible Mass Gapmentioning
confidence: 99%
“…For generality and to compare energy scales, we take into account a mass gap in the dispersion relation, which can be experimentally created, e.g., due to A-B sublattice asymmetry caused by SiC substrate or by regular deposition of impurities. 20,21 At zero magnetic field it was demonstrated that the pseudospin degree of freedom (due to valleys) produces diamagnetic susceptibility which is [22][23][24] …”
Section: Clean Graphene With Possible Mass Gapmentioning
confidence: 99%
“…However, recent research efforts have been directed towards not only the synthesis of graphene-like materials, but also towards the functionalization of existing ultra-thin crystal structures. These recent studies have revealed some important results such as (i) tunable bandgap opening in graphene, [22][23][24][25][26][27] (ii) H-defect-induced magnetization of graphane, 27,28 (iii) bandgap engineering in silicene and germanene, [29][30][31] (iv) stability enhancement in h-BN, 32 and (v) tunable magnetic features in TMDs.…”
Section: Introductionmentioning
confidence: 99%
“…However, first-principles computations based on the density functional theory (DFT) have revealed much richer electronic structures and predicted the subtle band gap opening due to individual set of structural parameters of a GNM, though the scaling rule for E g agrees in general with that derived from simple arguments. For instance, Ouyang et al 24 predicted half of GNMs were semi-metals and the rest were semiconductors, while Şahin et al 21 pointed out that only one third of their calculated GNMs had significant none-zero band gaps. Previous theoretical works haven't sufficiently consider GNMs systematically and thoroughly analyze the band-opening mechanism.…”
Section: Introductionmentioning
confidence: 99%